EFFECTS OF SODIUM INTAKE AND SMOKING HABITS ON THE BLOOD PRESSURE OF CORONARY HEART PATIENTS AT GRANDMED LUBUK PAKAM HOSPITAL - Panjaitan, Raini; Reni Novia; Andreais Boffil Cholilluloh; Adelina Sri Dewi Karo-Karo; Edarni Zebua (Fakultas Kesehatan Masyarakat Institut Kesehatan Medistra Lubuk Pakam, 2023)
Coronary heart disease (CHD) is a type of degenerative disease that causes death. The risk factor for CHD is high blood pressure which causes the workload of the heart pump to become heavy. The incidence of increased blood pressure is a factor of sodium intake and smoking habits. The aim of this research is to determine the relationship between sodium intake and smoking habits on the blood pressure of coronary heart patients in hospitals. Granmed Lubuk Pakam. The type of research used is quantitative research with a cross sectional design. The population in this study were patients suffering from coronary heart disease at Grandmed Lubuk Pakam Hospital. The sample used in this research was 47 respondents. The results show that the distribution based on the age category is the majority aged 38-48 years (44.7%), the gender category of CHD patients is the majority male (70.2%), the majority education category is high school graduates (55.3%), the pressure category The majority of patients' blood levels were pre-hypertensive and grade 1 hypertension (27.7%), respondents' sodium intake was high (55.3%), respondents had moderate smoking habits (42.6%). Based on the results of statistical analysis, it was found that there was a significant relationship between sodium intake and the blood pressure of CHD patients (p-value = 0.003) as well as the relationship between smoking habits (p-value = 0.030) and the blood pressure of coronary heart patients.ing habits (P-value = 0.030) with blood pressure in coronary heart patients.